Solar energy policy for india: An overview - KhareSaxena, Anupama; Saxena, Seema; Sudhakar, Kumarasamy (China Electric Power Research Institute, 2024)
India's energy crisis can be resolved by using reliable sources of renewable resources, such as solar energy with minimum adverse ecological effects. Several photovoltaic projects have been sanctioned based on rooftop models and land-based solar parks to address energy security concerns. India's strategy focusing on increasing the installation of new solar plants, lead to the vast expansion of the renewable energy market. This paper explores the Indian government policies, current approaches, significant achievements and a scenario for solar power in India. It also summaries various technological options, research, awareness and outreach activities for the deployment of solar energy. These supportive policies provide tax exemptions, attractive tariff plans, and economic incentives which contribute to the sustainable development of the nation.